Catalytic Upgrading of Biomass‐Derived Sugars with Acidic Nanoporous Materials: Structural Role in Carbon‐Chain Length Variation. Issue 2 (20th December 2018) - He, Jian; Li, Hu; Saravanamurugan, Shunmugavel; Yang, Song
Abstract: Shifting from petroleum‐based resources to inedible biomass for the production of valuable chemicals and fuels is one of the significant aspects in sustainable chemistry for realizing the sustainable development of our society. Various renowned biobased platform molecules, such as 5‐hydroxymethylfurfural, furfural, levulinic acid, and lactic acid, are successfully accessible from the transformation of biobased sugars. To achieve the specific reaction routes, heterogeneous nanoporous acidic materials have served as promising catalysts for the conversion of bio‐sugars in the past decade. This Review summarizes advances in various nanoporous acidic materials for bio‐sugar conversion, in which the number of carbon atoms is variable and controllable with the assistance of the switchable structure of nanoporous materials. The major focus of this Review is on possible reaction pathways/mechanisms and the relationships between catalyst structure and catalytic performance. Moreover, representative examples of catalytic upgrading of biobased platform molecules to biochemicals and fuels through selective C−C cleavage and coupling strategies over nanoporous acidic materials are also discussed. Abstract : Sweet success : The catalytic transformation of biobased sugars into biofuels and fine chemicals is a key aspect of biomass valorization. Owing to switchable structures, nanoporous acidic materials are promising heterogeneous catalysts for converting saccharides into organic products with variable and controllable numbers of carbon atoms. Recent advances in the production of value‐added molecules from biomass‐derived sugars over nanoporous acidic materials are presented.